Green Synthesis and Characterization of Carbon Dots Nanosensors Using Pumpkin Seed Shell for Spectrofluorimetric Determination of L-cysteine - Afsaneh Zarei Manujan; Alireza Bazmandegan-shamili; Mohammad Sabet; Masoud Rohani Moghadam (شیمی کاربردی روز)
In this research, carbon dots with high luminescence intensity were synthesized using pumpkin seed shell as a new and green source with hydrothermal method. The prepared carbon dots were characterized using X-ray diffraction, Fourier transform infrared spectroscopy and Scanning electron microscopy. The average size of the synthesized carbon dots was estimated about 59 nm. In addition, the luminescence property of the synthesized carbon dots was evaluated using photoluminescence analysis and according to their high luminescence property at excitation wavelength of 340 nm and emission wavelength of 425 nm, they were used as nanosensor for the determination of L-cysteine. By addition of L-cysteine, the emission intensity of carbon dots solution was reduced. In order to enhancement of the method sensitivity, the effective parameters on the quenching intensity of L-cysteine such as pH, interaction time and environment ionic strength were examined and optimized. Under the laboratory optimum conditions, linear range of 5-500 µM, limit of detection of 1.0 µM and relative standard deviation (at 10 µM of L-cysteine) of 3% was obtained. The accuracy of the proposed method was evaluated using spiking procedure and according to the recoveries percent (96-102), the proposed method is a reliable method for determination of L-cysteine in the examined samples. Finally, the prepared nanosensor was successfully used for the determination of L-cysteine in tap water samples.